A Contemporary Framework for Integrating Maqāṣid al-Sharīʿah and ESG in Designing Sharia Capital Market Indices - Lilis Renfiana; Mohammad Ridwan; Ali Akram kadhim; Saleem Asouli; Noor Snober; Misnen Ardiansyah (Faculty of Sharia, UIN Jurai Siwo Lampung, 2026)
This study develops a contemporary framework for integrating Maqāṣid al-Sharīʿah with Environmental, Social, and Governance (ESG) principles in the design of Sharia capital market indices. It addresses the persistent gap between formalistic Sharia screening—primarily concerned with legal compliance—and the materiality-driven logic of ESG, which emphasizes sustainability impact. Employing a qualitative conceptual approach, the study constructs a Three-Tier Framework that repositions Maqāṣid al-Sharīʿah as the teleological foundation of sustainability assessment. The framework is operationalized into a systematic blueprint comprising four integrative themes and 22 measurable indicators. These indicators are derived from a thematic clustering of 45 elements from the Maqāṣid al-Sharīʿah Research Index (MSRI) and subsequently aligned with internationally recognized standards, including the Global Reporting Initiative (GRI) and the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI). The alignment process applies two criteria: dual relevance to both Maqāṣid and ESG dimensions, and the availability of verifiable public data. Preliminary validation through case studies of PT Bukit Asam and Unilever Indonesia demonstrates the framework’s ability to differentiate sustainability performance across sectors while revealing substantive gaps in current Sharia reporting practices, particularly in narrative depth and impact orientation. Unlike prior studies that position Maqāṣid and ESG as parallel constructs, this research reconstructs the evaluative logic by embedding Maqāṣid as the ethical core of ESG integration. This study contributes both theoretically and practically by advancing an integrated paradigm for Islamic finance and offering a replicable model for index construction. It provides a conceptual and operational foundation for transforming Sharia capital markets toward a more holistic, impact-oriented, and ethically grounded sustainability assessment system.